2020
DOI: 10.1016/j.isci.2020.101734
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics Identifies Neuronal and Metabolic Adaptations to Hypergravity and Microgravity in Caenorhabditis elegans

Abstract: Deep space exploration is firmly within reach, but health decline during extended spaceflight remains a key challenge. In this study, we performed comparative transcriptomic analysis of Caenorhabditis elegans responses to varying degrees of hypergravity and to two spaceflight experiments (ICE-FIRST and CERISE). We found that progressive hypergravitational load concomitantly increases the extent of differential gene regulation and that subtle changes in 1,000 genes are reproducibly observed during spaceflight-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…They have been found to demonstrate highly comparable molecular and physiological maladaptations to spaceflight that are parallel to those observed in people. For example, we have shown the nematode Caenorhabditis elegans grown in mG displays reduced muscle cytoskeletal proteins, mitochondrial metabolic enzymes (Higashibata et al, 2016), and DAF-2/insulin/IGF-1 signaling (Willis et al, 2020). This molecular profile translates to impaired muscular performance and body length (Higashibata et al, 2016), paralleling functional changes reported in astronauts (Fitts et al, 2010;Nicogossian et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…They have been found to demonstrate highly comparable molecular and physiological maladaptations to spaceflight that are parallel to those observed in people. For example, we have shown the nematode Caenorhabditis elegans grown in mG displays reduced muscle cytoskeletal proteins, mitochondrial metabolic enzymes (Higashibata et al, 2016), and DAF-2/insulin/IGF-1 signaling (Willis et al, 2020). This molecular profile translates to impaired muscular performance and body length (Higashibata et al, 2016), paralleling functional changes reported in astronauts (Fitts et al, 2010;Nicogossian et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…However, in space-flown animals, we observed a reversal in exopher-genesis rate between ALMR and ALML neurons. Although the reason underlying this reversal is unclear, a recent study of reproducible transcriptomic changes in space-flown C. elegans ( Willis et al., 2020 ) identified downregulated genes predicted to be under the control of the transcription factor NSY-7, which is involved in determination of neuronal left/right asymmetry ( Lesch et al., 2009 ). Together, these results suggest that spaceflight may influence the left/right asymmetries in the C. elegans nervous system and potentially affect side-specific neuronal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason underlying this reversal is unclear, a recent study of reproducible transcriptomic changes in space-flown C. elegans (Willis et al, 2020) identified downregulated genes predicted to be under the control of the transcription factor NSY-7, which is involved in determination of neuronal left/right asymmetry (Lesch et al, 2009). Together, these results suggest that spaceflight may influence the left/right asymmetries in the C. elegans nervous system and potentially affect side-specific neuronal functions.…”
Section: Clearance Of Neuronal Waste Is Not Affected By Spaceflight In Normal Conditionsmentioning
confidence: 90%